Evaluasi Klon-Klon Tebu Potensial di Lahan Kering - ,, Djumali; Heliyanto, Bambang; Khuluq, dan Ahmad Dhiaul (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2018)
The candidates for new superior varieties are  expected to be able to increase the sugar yield in the upland area. Germplasm evaluation has indicated some clones had potentially high sugar yield in upland area. The study was conducted at Asembagus Experimental Station, Situbondo Regency, East Java, from December 2016 to November 2017. The study aimed to obtain sugarcane clones with higher sugar yield than existing varieties on upland area. Twelve potential sugarcane clones (17, 87, 90, 104, 212, 351, 354, 451, 452, PBG 2, 386 SOF 1118, and 400 SOF 1132) and 2 check varieties (PS 881 and Cenning) were arranged in a randomized block design with three replicates. The results showed that the sugarcane production of 104, 212, and PBG 2 clones  (97.42-98.26 ton ha-1) were not different from productivity of Cenning (105.42 ton ha-1) but they were higher than that of PS 881 (75.68 ton ha-1). The sugar content  of 104 and PBG 2 clones (9.43-9.46%) was higher than Cenning (6.94%) but lower than PS 881 (11.66%). The sugar yields (9.16-9.24 ton ha-1) of 104 and PBG 2 clones were higher than Cenning (7.47 ton ha-1) but they were not different from PS 881 (8.84 ton ha-1).